(untitled) (Research, Society and Development, 2022)
Ensuring vaccination of approximately 90% of adolescents for the human papillomavirus (HPV) by 2030 is a key strategy put forth by the World Health Organization (WHO) for the elimination of cervical cancer. This study aims to analyze the extent of vaccination in 25– 29-year old women by 2030, considering that the vaccination campaign began in 2014. Data regarding the HPV vaccination of women born between 2001 and 2005 were obtained from the Information System of the Ministry of Health on the female population projection for 2026–2030. Considering only the first dosage, the South, Southeast, and Northeast regions will have reached the target of 90% coverage. However, regarding the second dose, only the Southeast region was have reached the 89.7% target in 2030. However, the Midwest and North regions will only have 68.8% and 67.01% coverage, respectively; therefore, the vaccination drive must be strictly implement for these regions.